Ismail Gasprali's Jadidic Ideas And Its Influence On The Lives Of Turkic And Muslim Peoples (Eurasian Journal of History, Geography and Economics, 2026)
This article analyzes the ideas and goals of the Jadid movement, its strategic mission, and its impact on world civilization, particularly the lives of Turkic Muslim peoples, based on sources from that period. It examines the fact that Jadidism was a unique phenomenal phenomenon.